2009
DOI: 10.1158/1940-6207.capr-08-0155
|View full text |Cite
|
Sign up to set email alerts
|

Anthocyanins in Black Raspberries Prevent Esophageal Tumors in Rats

Abstract: Diets containing freeze-dried black raspberries (BRB) suppress the development of N-nitrosomethylbenzylamine (NMBA)-induced tumors in the rat esophagus. Using bioassay-directed fractionation, the anthocyanins in BRB were found to be the most active constituents for down-regulation of carcinogen-induced nuclear factor-κB and activator protein-1 expression in mouse epidermal cells in vitro. The present study was undertaken, therefore, to determine if the anthocyanins contribute to the chemopreventive activity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
182
2
6

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 181 publications
(200 citation statements)
references
References 29 publications
10
182
2
6
Order By: Relevance
“…Their content in the powder was: cyanidin-3-glucoside (278.5 mg/100 g dry weight [DW]), cyanidin-3-sambubioside (56.0 mg/100 g DW), cyanidin-3-rutinoside (1,790 mg/100 g DW), and cyanidin-3-xylosylrutinoside (853.5 mg/100 g DW), resulting in a total anthocyanin content of 2,978 mg/100 g DW. We have shown previously that the anthocyanins in BRBs are chemopreventive in a rat model of esophageal cancer (22).…”
Section: Methodsmentioning
confidence: 91%
“…Their content in the powder was: cyanidin-3-glucoside (278.5 mg/100 g dry weight [DW]), cyanidin-3-sambubioside (56.0 mg/100 g DW), cyanidin-3-rutinoside (1,790 mg/100 g DW), and cyanidin-3-xylosylrutinoside (853.5 mg/100 g DW), resulting in a total anthocyanin content of 2,978 mg/100 g DW. We have shown previously that the anthocyanins in BRBs are chemopreventive in a rat model of esophageal cancer (22).…”
Section: Methodsmentioning
confidence: 91%
“…The evidence from a previous study shows that 5% whole freeze-dried black raspberries and the anthocyanin-rich fraction supplemented to N-nitrosomethylbenzylamine-induced F344 rats have chemopreventive potential, where the treatment groups inhibit cell proliferation, inflammation, angiogenesis, and induce apoptosis in both preneoplastic and papillomatous esophageal tissues [75]. Thus anthocyanins have chemoprophylaxis potential.…”
Section: Nutraceutical and Pharmaceutical Effects Of Anthocyaninsmentioning
confidence: 99%
“…Preclinical studies in our laboratory have shown that a chemopreventive approach using whole fruits and vegetables or their natural constituents has potential for prevention of esophageal SCC. Specifically, we have demonstrated the effectiveness of black raspberries (BRB) and their bioactive components in preventing the development of N-nitrosomethylbenzylamine (NMBA)-induced esophageal squamous cell papillomas in rats, some of which progress to carcinomas (3)(4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms by which BRBs and their component ACs impede tumorigenesis in the rat esophagus include reducing inflammation, cell proliferation, and angiogenesis, as well as stimulating apoptosis, cell differentiation, and cell adhesion (6). The inhibitory effects that BRBs and ACs have on inflammatory and angiogenic biomarkers in the esophagus are especially profound, including their ability to modulate the mRNA and protein expression of COX-2, inducible nitric oxide synthase (iNOS), NF-kB, IL1b, soluble epoxide hydrolase (sEH), pentraxin-3 (PTX3), CD34, VEGF, and HIFa (6)(7)(8)(9). BRB ACs are more effective at reducing inflammation than 5-aminosalicyclic acid, a common anti-inflammatory drug in vitro (10).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation